COVID-19 and Islamic Finance - Hassan, M. Kabir 1963-; Aishath Muneeza 1983- (Cambridge elements, 2022)
The objective of this Element is to provide an overview of Islamic finance by highlighting the impact of the pandemic on it in a comprehensive manner by looking at two branches of Islamic finance: Islamic commercial finance; and Islamic social finance. The approach that is adopted in this Element is to first provide an overview of Islamic finance to the readers in a simple and easy manner followed by the impact of pandemic discussed separately for both types of Islamic finance. Last, but not least, the Element also recommends ways in which Islamic finance could be further improved in the light of the lessons learnt from the pandemic. It is anticipated that the recommendations made in this regard would assist policymakers, practitioners, researchers and other stakeholders of Islamic finance to understand the way to unlock the full potential of Islamic finance to reduce the wealth gap and achieve financial inclusion